2010
DOI: 10.1002/app.32613
|View full text |Cite
|
Sign up to set email alerts
|

Novel grafted nafion membranes for proton‐exchange membrane fuel cell applications

Abstract: Novel poly(glycidyl methacrylate)-grafted Nafion-phosphoric acid membranes for direct-oxidation methanol fuel cells were prepared with a potassium persulfate chemical initiation system for the first time. The introduced epoxy groups were converted to amine groups through a reaction with ethylenediamine, which consequently doped with phosphoric acid (APO 3 H) groups. The latter significantly contributed to enhancing the ionexchange capacity, mechanical properties, and thermal stability. Factors affecting the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Therefore, the operating temperature of the LT-PEM is normally not higher than 100 °C [30,31,32,33]. The Nafion ® membrane is the most commonly used LT-PEM in fuel cells [34,35,36,37,38]. Previously, we reported a different type of polymer electrolyte membranes, which was prepared by activation of ETFE base material with electron beam (EB) treatment, subsequent graft radical copolymerization of methacrylate monomers on ETFE followed by sulfonation to introduce protogenic groups [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the operating temperature of the LT-PEM is normally not higher than 100 °C [30,31,32,33]. The Nafion ® membrane is the most commonly used LT-PEM in fuel cells [34,35,36,37,38]. Previously, we reported a different type of polymer electrolyte membranes, which was prepared by activation of ETFE base material with electron beam (EB) treatment, subsequent graft radical copolymerization of methacrylate monomers on ETFE followed by sulfonation to introduce protogenic groups [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Further increase in the polymerization time had no effect due to the free radicals adsorption on the precipitated polymer particles. Thus, high termination step rate was over the rate of polymerization step . The reaction progress during time caused the initiator and comonomers consumption, decreasing the reaction rate till reaching a constant value at which more time has a negligible effect on the conversion yield.…”
Section: Resultsmentioning
confidence: 89%
“…[22] While copolymerization between AN with DVB yielded about 80%. [26] The reaction progress during time caused the initiator and comonomers consumption, decreasing the reaction rate till reaching a constant value at which more time has a negligible effect on the conversion yield. [20] So, the conversion yield increased in the sequence: PAN < poly (AN-co-MMA) < poly (St-co-AN) < poly (AN-co-DVB).…”
Section: Effect Of Polymerization Temperaturementioning
confidence: 99%
“…The surface of both CS and SA membranes appear to have a smooth and homogeneous surface and haven't any cracks [19,23]. Ion-exchange capacity indicates the density of ionizable hydrophilic groups in the membrane matrix, which are responsible for the IC of the membranes, and this is an indirect approximation of the proton conductivity [20,[24][25][26][27].IEC results of CS and SA membranes were reported to be 1.54 and 1.04(meq/g), respectively. This result showed that the membranes have good IEC and suitable for using in the separation application technique.…”
Section: Polymeric Separation Of Ethanol-water Mixture 331 Membranmentioning
confidence: 99%